Homeopathic Preparations to Control the Rosy Apple Aphid (Dysaphis plantaginea Pass.). (2010) - Wyss, Eric; Tamm, Lucius; Siebenwirth, Joachim; Baumgartner, Stephan
Abstract : A laboratory model system with the rosy apple aphid ( Dysaphis plantaginea Pass.) on apple seedlings was developed to study the effects of homeopathic preparations on this apple pest. The assessment included the substance Lycopodium clavatum and a nosode of the rosy apple aphid. Each preparation was applied on the substrate surface as aqueous solution of granules (6c, 15c, or 30c). Controls were aqueous solutions of placebo granules or pure water. In eight independent, randomized, and blinded experiments under standardized conditions in growth chambers, the development of aphids on treated and untreated apple seedlings was observed over 17 days, each. Six experiments were determined to assess the effects of a strict therapeutic treatment; two experiments were designed to determine the effects of a combined preventative and therapeutic treatment. After application of the preparations, the number of juvenile offspring and the damage on apple seedlings were assessed after 7 and 17 days, respectively. In addition, after 17 days, the seedling weight was measured. In the final evaluation of the six strictly therapeutic trials after 17 days, the number of juvenile offspring was reduced after application of L. clavatum 15c (-17%, p = 0.002) and nosode 6c (-14%, p = 0.02) compared to the pure water control. No significant effects were observed for leaf damage or fresh weight for any application. In the two experiments with combined preventative and therapeutic treatment, no significant effects were observed in any measured parameter. Homeopathic remedies may be effective in plant-pest systems. The magnitude of observed effects seems to be larger than in models with healthy plants, which renders plant-pest systems promising candidates for homeopathic basic research. For successful application in agriculture, however, the effect is not yet sufficient. This calls for further optimization concerning homeopathic remedy selection, potency level, dosage, and application routes.